PENDIDIKAN AGAMA KELUARGA PENGRAJIN LIMBAH ALAM DI KOTA TERNATE - Asnandar Abubakar (Balai Penelitian dan Pengembangan Agama Makassar, 2017)
This study aims to see the reality of religious education in the family of craftsmen inTernate City, the family of Ibu Ulfa, a craftsman by utilizing natural waste. Thisresearch is qualitative research. This study takes a case study that focuses on theoverall religious activity of the artisans studied. The data collected through theobservation and interview activities then analyzed interactively and lastedcontinuously to complete. Religious education in the family can be seen from theaspect of aqidah, akhlak, syariah. Experience and understanding of this religion thenseen his transformation of religious education through cognitive, affective, andpsychomotor aspects. Aqidah is seen from the level of family belief in Allah SWT.morality seen from the attitude and personal behavior when faced with the reality oflife. And sharia is seen how far social relationships with others. The role of parents isalso very influential in the transformation of children's religious education toknowledge, attitude and behavior patterns of children in community life. Religiouseducation from parents instills a sense of religiousness in children so that bit by bitwill be attached to the values of religion in children. And will build good characterand positive behaviors in the association.